Comparison of water quality status between two different types of river: a case study of Kemasin River and Pengkalan Chepa River - Morsad, Nadzirah (2014)
Water quality refers to the physical, chemical and biological status of the water body. Water quality Kemasin River (KR) affected by active agricultural activities while the Pengkalan Chepa River (PCR) is influenced by urban development and accommodation of crowded with heavy population since it is situated in the urban area. The aim of this study was to determine the characteristics of water quality of KR and PCR as well as to determine the relationship status of water quality parameters between KR and PCR. In addition, this study was to classify current status water quality for KR and PCR based on the Water Quality Index (WQI). Sampling was carried out for a month on January 2014. For each sampling activities, water sample collections were done twice. Three sampling locations along the KR and PCR were selected as sampling stations. For KR sampling station consists of Kg.Bangu (Station 1), Pengkalan Cina (Station 2) and Pengkalan Petah (Station 3). For PCR the sampling stations consists of Sg.Keladi (Station 1), Kg. Baung (Station 2) and Kg.Pulau Panjang (Station 3). Six water quality parameters: Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammonia Nitrogen (NH3-N), Total Suspended Solids (TTS) and pH were analyzed based on insitu and ex-situ analysis. Statistical analysis of independent t -test indicated that there were significant differences of BOD, NH3-N, TSS and pH between KR and PCR. The results of water quality indicated that most of the water quality parameters higher at PCR compared to KR. Currently WQI status for KR (65.48) was found better than the PCR (44.71). WQI of KR was categories under class III while PCR was categories under class IV that considered slightly polluted. The water quality status of KR was affected due to active agricultural activities throughout the year and for PCR was polluted due to land use activities from urban and industrial areas. In a conclusion, the water quality of KR and PCR should be monitored extensively by the authorities and pollution control and effective management of the river should be implemented with the cooperation of the public and local authorities.